Type-2 Diabetes and Gene Therapy: The Promise of CRISPR Gene Therapy in type-2 Diabetes Mellitus - Sikandar Hayat Khan (Journal of Obesity Management, 2019)
Gene therapy has entered a new era with the dawn of CRISPR/Cas9 technology which though were always available in nature but rediscovered to tame into a real-tlife genome editing tool. With the modernization upsurge and changes in ways the “homo sapiens” survived on this planet from hunger to current era of exuberance has led to multiple metabolic issues like type-2 diabetes. Notwithstanding the rapid emergence of medication to suppress the hyperglycemia and insulin resistance associated with this menace, need has definitely emerge to find more personalized and curative dimensions to therapeutics of type-2 diabetes mellitus. Gene therapy is one more addition to Type-2 Diabetes Mellitus (T2DM) therapy, where multiple options have emerged in the shape of microRNA, direct knocking out of cellular structures like proteins and enzymes and very recently the precision nucleases associated with CRISPR technologies. This mini-review attempt to summarize some of the recent examples of gene therapy with major focus on CRISPR/Cas technologies.
Keywords: Gene therapy